Brooke Shields is not allowed to get old : thoughts on aging as a woman - Shields, Brooke, 1965-; Bertsche, Rachel (Flatiron Books, 2025)
"From Brooke Shields, the icon who has inspired generations of women, comes a thoughtful, intimate, and candid exploration of the humility and power of aging"--